Disassembly, refinement, and reassembly: From ancient papermaking to modern materials processing - Jing Shen; Meiyun Zhang (Journal of Bioresources and Bioproducts)
Papermaking, a cornerstone of human civilization and one of China's Four Great Inventions, exemplifies the enduring legacy of ancient ingenuity in shaping modern materials science. Originating from the groundbreaking work of Lun Cai and his team, the papermaking process involves the meticulous disassembly, refinement, and reassembly of natural fibers into cohesive sheets: a process that, while refined, has remained fundamentally unchanged for nearly 2 000 years. This work explores the pivotal role of papermaking in contemporary society within the broader context of materials science, highlighting its fundamental principles and the remarkable versatility of its scalable process. Papermaking, once central to the dissemination of knowledge worldwide, has now evolved into a key player in the sustainable production of environmentally friendly products, touching every aspect of modern life. The principles underlying papermaking have inspired the development of novel materials, with techniques such as vacuum filtration paving the way for innovations like nanopapers based on a diverse group of building blcoks. Looking ahead, the field presents significant opportunities in sustainable sourcing, the creation of eco-friendly packaging, and the development of advanced materials with applications in healthcare and beyond. The enduring relevance of papermaking lies in its adaptability, versatility, and boundless potential for future innovation.